Analysis of the Implementation of the Merah Putih Cooperative in Kagungan Village - Kusumawati, Destri; Agustino, Leo; Sjafari, Agus (Indonesian Journal of Social Science Research, 2026)
The Merah Putih Cooperative was established in response to various economic challenges faced by the community in Kawungan Village, Serang City, Banten. The formulation of the main problem faced is how these cooperatives can contribute to improving the welfare of members and reducing poverty rates in the area. According to data from the Central Statistics Agency (BPS) in 2021, the poverty rate in Banten Province reached 8.22%, with Serang City being one of the areas with a poverty rate above the provincial average (BPS, 2021). The Merah Putih Cooperative is expected to be an alternative solution to improve the economic condition of the community, especially in providing access to capital and markets for local products. The Merah Putih Cooperative is one of the initiatives that aims to improve the welfare of the community in Kagungan Village. This study aims to analyze the implementation of these cooperatives, as well as their impact on poverty alleviation in the region. The method used in this study is a qualitative approach with data collection through interviews, observations, and document analysis. The results of the study show that this cooperative has made a significant contribution in increasing members' income and reducing poverty rates. The conclusion of this study emphasizes the importance of government support and active participation of the community in the sustainability of cooperatives.